2015
DOI: 10.3126/jngmc.v12i1.13402
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Obesity Among Type 2 Diabetes Patients Attending Diabetic Clinic in Nepalgunj Medical College Teaching Hospital

Abstract: Background: Obesity and type 2 diabetes constitute major public health issues in modern societies worldwide. These two forms frequently coexist, and statistics show that 60–90% of all patients with type 2 diabetes are or have been obese. Obesity is generally considered to be a strong risk factor for the development of type 2 diabetes mellitus in future.Objectives: This study aims to assess the prevalence of obesity among type 2 diabetes patients attending diabetic clinic in Nepalgunj Medical College Teaching H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
2
2
0
Order By: Relevance
“…27 It is also comparable to a study by Parajuli et al in a health facility-based cross-sectional study among 277 type 2 diabetics in Nepal, where about one-third of the participant (37.1%) were also overweight. 28 The findings in the index study is also similar to a study by Omotoye et 13,29 This may be because obesity or overweight is a risk factor for type 2 diabetes and may occur along with comorbidities as seen in metabolic syndrome. 30 In the index study, the majority of the participants had prehypertension.…”
Section: Discussionsupporting
confidence: 86%
“…27 It is also comparable to a study by Parajuli et al in a health facility-based cross-sectional study among 277 type 2 diabetics in Nepal, where about one-third of the participant (37.1%) were also overweight. 28 The findings in the index study is also similar to a study by Omotoye et 13,29 This may be because obesity or overweight is a risk factor for type 2 diabetes and may occur along with comorbidities as seen in metabolic syndrome. 30 In the index study, the majority of the participants had prehypertension.…”
Section: Discussionsupporting
confidence: 86%
“…Our study shows, of 175 adult diabetic patients who were followed, obesity was found in of 43,40%. In consistent with these studies in 385, 82, 160 type 2 diabetic patients which showed that the prevalence of obesity were respectively 4,2%, 11%, 14,4% [1,20,21]. However, higher prevalence was reported in one of the study done, the majority (83%) of the 212 type 2 diabetic patients were obese [7].…”
Section: Discussionsupporting
confidence: 70%
“…On a total of 385 patients diabetics between 40-49 years, 50-59 years then 60 years and more there are respectively 30,6%, 28,3% and 34,3% of obese [21]. And, in a cohort of 4098 diabetic patients between 45-54 years, 55-64 years then 65 years and more there are respectively 20,1%, 29,4% and 40,6% of obese [28].…”
Section: Discussionmentioning
confidence: 99%
“…Worldwide, obesity and type 2 diabetes constitute the major public health issues in modern societies, and are said to frequently coexist, with statistics showing that approximately 60-90% of all patients with type 2 diabetes are obese or at high risk of developing obesity [ 23 ]. However, an accurate diagnosis of body fat composition requires expensive equipment and specialised skills and, in certain situations, exposure to potentially hazardous radiations [ 24 ].…”
Section: Discussionmentioning
confidence: 99%